The Dual Roles of Human γδ T Cells: Anti-Tumor or Tumor-Promoting - Li, Yang; Li, Gen; Zhang, Jian; Wu, Xiaoli; Chen, Xi (Frontiers in Immunology, 2021)
γδ T cells are the unique T cell subgroup with their T cell receptors composed of γ chain and δ chain. Unlike αβ T cells, γδ T cells are non-MHC-restricted in recognizing tumor antigens, and therefore defined as innate immune cells. Activated γδ T cells can promote the anti-tumor function of adaptive immune cells. They are considered as a bridge between adaptive immunity and innate immunity. However, several other studies have shown that γδ T cells can also promote tumor progression by inhibiting anti-tumor response. Therefore, γδ T cells may have both anti-tumor and tumor-promoting effects. In order to clarify this contradiction, in this review, we summarized the functions of the main subsets of human γδ T cells in how they exhibit their respective anti-tumor or pro-tumor effects in cancer. Then, we reviewed recent γδ T cell-based anti-tumor immunotherapy. Finally, we summarized the existing problems and prospect of this immunotherapy.